2002
DOI: 10.1039/b206648c
|View full text |Cite
|
Sign up to set email alerts
|

New supramolecular organization for a glycoluril: chiral hydrogen-bonded ribbons

Abstract: A series of substituted glycoluril molecules exhibits a substantial twist of the fused five-membered rings and assembles exclusively chiral hydrogen-bonded ribbons in the solid-state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…The most unusual structural feature of (I) is the boat conformation of its cyclohexyl ring imposed by the ring fusion at C2ÐC4. The remaining structural features of (I) are similar to those reported previously for related benzylated glycolurils Johnson et al, 2002).…”
Section: Commentsupporting
confidence: 84%
See 1 more Smart Citation
“…The most unusual structural feature of (I) is the boat conformation of its cyclohexyl ring imposed by the ring fusion at C2ÐC4. The remaining structural features of (I) are similar to those reported previously for related benzylated glycolurils Johnson et al, 2002).…”
Section: Commentsupporting
confidence: 84%
“…The glycoluril skeleton has served as an important building block for the preparation of a wide variety of supramolecular assemblies, including molecular clips (Rowan et al, 1999;Wu, Chakraborty et al 2002), molecular capsules (Hof et al, 2002), xerogels (Ko È lbel & Menger, 2001), the cucurbit[n]uril family (Freeman et al, 1981;Kim et al, 2000;Day et al, 2001;Lagona et al, 2003), and, most recently, anion-binding receptors (Kang et al, 2004). Recently, we and others Johnson et al, 2002Johnson et al, , 2003Moon et al, 2003) have demonstrated that dialkylated glycoluril derivatives form hydrogen-bonded tapes in the solid state when crystallized from solvents that do not contain strong hydrogen-bond donor or acceptor groups. In this paper, we report the crystal structure of o-xylylene-derived glycoluril, (I), which contains a fused cyclohexane ring on its convex face.…”
Section: Commentmentioning
confidence: 99%
“…These rings bear two CO 2 Et groups in (I) and two Ph groups in (II) on their`convex' faces. The bond lengths and angles in both compounds are similar to those reported previously (Johnson et al, 2002(Johnson et al, , 2003Wu et al, 2002;Wang et al, 2006;Chen et al, 2007). The OÁ Á ÁO distances are 5.657 (2) A Ê in (I) and 5.691 (2) A Ê in (II).…”
Section: Commentsupporting
confidence: 87%
“…Rebek and co-workers have reported that achiral glycolurils form chiral hydrogen-bonded ribbons in the solid state, and subsequently observed four complementary hydrogen bonds between sulfamides and ureas linking adjacent hydrogenbonded ribbons (Johnson et al, 2002(Johnson et al, , 2003. Isaacs and coworkers have reported similar hydrogen-bonded ribbons in a related syn-protected glycoluril derivative (Wu et al, 2002).…”
Section: Commentmentioning
confidence: 99%
“…Glycoluril and its derivatives have found widespread use in supramolecular chemistry including the preparation of cucurbiturils (Freeman et al, 1981;Kim et al, 2000;Day et al, 2001), molecular capsules (Hof et al, 2002), molecular clips (Rowan et al, 1999), and xerogels (Ko È lbel & Menger, 2001). Recent studies even suggest that glycoluril derivatives have signi®cant potential in crystal engineering studies (Wu et al, 2002;Johnson et al, 2002). Our group has prepared a series of glycoluril bis(cyclic ethers) bearing carboxylic acid derived functional groups (acid, ester, amide, and imide) on their convex face as novel monomers for the synthesis of cucurbit[n]uril derivatives (Burnett et al, 2003) and analogs (Lagona et al, 2003).…”
Section: Commentmentioning
confidence: 99%